2010
DOI: 10.1002/pc.20944
|View full text |Cite
|
Sign up to set email alerts
|

Void formation model and measuring method of void formation condition during hot pressing process

Abstract: For resin matrix composites, voids are common defects that can seriously deteriorate the properties of the composite parts. Thus, the elimination of voids is a crucial element in controlling the manufacturing process of composite parts. This article focuses on void formation originating from hygroscopic water for resin matrix composite laminates prepared with hot pressing process. The Kardos void formation model was developed to analyze the critical resin pressure for the initiation of voids, and the influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…The voids formation mechanisms of carbon fiber‐reinforced composites have been intensively studied . Experimental results showed that small and spherical voids came from prepreg, either present before consolidation or generated by diffusion of water vapor during forming process, while large and elongated voids resulted from air entrapment and wrinkles created during lay‐up .…”
Section: Introductionmentioning
confidence: 99%
“…The voids formation mechanisms of carbon fiber‐reinforced composites have been intensively studied . Experimental results showed that small and spherical voids came from prepreg, either present before consolidation or generated by diffusion of water vapor during forming process, while large and elongated voids resulted from air entrapment and wrinkles created during lay‐up .…”
Section: Introductionmentioning
confidence: 99%
“…And the manufacturing knowledge applied to the quality manufacturability analysis should be exploited further based on guidelines, empirical data, statistical data and physical models. In addition, it is also necessary to develop a software tool to effectively support this methodology and provide a user interface to perform the manufacturability evaluation for the composite Table 3 Experimental results of glass fiber/epoxy 648 laminates [16] Sample no.…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al [16] studied the effects of four quality indices such as relative humidity of prepreg, isothermal temperature T 2 and dwell time t 2 , as well as lay-up type of laminate and the applied pressure P 2 on the void formation based on the orthogonal experiment for epoxy 648 laminates. From the experiment results shown in Table 3, the applied pressure P 2 has the largest influence on void content.…”
Section: Analyzing the Quality Sensitivitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the resin pressure in the laminate increases with the improving slippage ability. This is helpful to eliminate the formation of voids in autoclave process [20].…”
Section: Elastic Modulus Of the Shear Layermentioning
confidence: 99%